2020
DOI: 10.1002/cre2.336
|View full text |Cite
|
Sign up to set email alerts
|

Risk of incident cardiovascular disease in people with periodontal disease: A systematic review and meta‐analysis

Abstract: Objectives Cardiovascular disease (CVD) is a major cause of mortality; periodontal disease (PD) affects up to 50% of the world's population. Observational evidence has demonstrated association between CVD and PD. Absent from the literature is a systematic review and meta‐analysis of longitudinal cohort studies quantifying CVD risk in PD populations compared to non‐PD populations. To examine the risk of incident CVD in people with PD in randomised controlled trials and longitudinal cohort studies. Material and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 94 publications
(86 reference statements)
7
52
1
1
Order By: Relevance
“…Among the same adult population, systemic diseases including cardiovascular disease (CVD), hypertension, diabetes, and inflammatory diseases are also highly prevalent (GBD 2019 Diseases and Injuries Collaborators, 2020). Robust evidence has shown that periodontitis is associated with increased risk of a number of systemic diseases (Borgnakke et al, 2013; Aguilera et al, 2019; Larvin et al, 2020a). This may be due to shared risk factors between conditions, alternatively periodontitis may be a risk factor for developing systemic diseases (Esteves‐Lima et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among the same adult population, systemic diseases including cardiovascular disease (CVD), hypertension, diabetes, and inflammatory diseases are also highly prevalent (GBD 2019 Diseases and Injuries Collaborators, 2020). Robust evidence has shown that periodontitis is associated with increased risk of a number of systemic diseases (Borgnakke et al, 2013; Aguilera et al, 2019; Larvin et al, 2020a). This may be due to shared risk factors between conditions, alternatively periodontitis may be a risk factor for developing systemic diseases (Esteves‐Lima et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, periodontal disease has emerged as a prototypical chronic infectious-inflammatory condition that may impact cerebrovascular health. Periodontitis is a chronic inflammatory disorder caused by polybacterial colonization and repeated low-grade exposure to gram-negative bacteria, leading to an increase in systemic inflammation [ 10 •]. A meta-analysis of 30 longitudinal cohort studies showed a modest but consistently increased risk of stroke by 1.24-fold in populations with periodontal disease [ 10 •].…”
Section: Systemic Infection and Stroke Riskmentioning
confidence: 99%
“…Periodontitis is a chronic inflammatory disorder caused by polybacterial colonization and repeated low-grade exposure to gram-negative bacteria, leading to an increase in systemic inflammation [ 10 •]. A meta-analysis of 30 longitudinal cohort studies showed a modest but consistently increased risk of stroke by 1.24-fold in populations with periodontal disease [ 10 •]. In an Atherosclerosis Risk in Communities analysis, periodontal disease was associated particularly with cardioembolic and thrombotic stroke subtypes [ 11 ].…”
Section: Systemic Infection and Stroke Riskmentioning
confidence: 99%
“…The first to raise the link between myocardial infarctions and poor oral health were Mattila et al in 1989 [77]. Since then, numerous studies have concluded a positive association between periodontal diseases and CVD independently of their common risk factors (smoking, age, diabetes) [75,[78][79][80][81]. Moreover, periodontal treatment has been shown to have beneficial effects on cardiovascular biochemical parameters such as endothelial function and C-Reactive Protein (CRP) levels [82][83][84][85].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%